2022
DOI: 10.1063/5.0084792
|View full text |Cite
|
Sign up to set email alerts
|

Design and reactive magnetron sputtering of thermochromic coatings

Abstract: Thermochromic coatings based on vanadium dioxide exhibit great potential in various fields, including smart energy-saving windows with temperature-dependent transmittance in the infrared at preserved transmittance in the visible. However, these promises come with challenges concerning the low-temperature preparation of high-quality crystalline VO2-based films by industry-friendly techniques and the simultaneous optimization of all coating characteristics, such as thermochromic transition temperature, luminous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 104 publications
0
16
0
Order By: Relevance
“…More recently, Kolenaty et al [13] demonstrated that when an HiPIMS-deposited VO 2 film was doped with W, multilayer smart windows with a thermochromic transition temperature of around 20-21 • C could be fabricated. Doping with W involved the use of DC sputtering concurrently with HiPIMS, offering more flexibility in terms of controlling the doping content in VO 2 films, and the processing temperature of the W-doped VO 2 was 330 • C. These results are important not only for the preparation of smooth films needed in optical devices, as demonstrated by Kolenaty et al, but also because magnetron sputtering is a well-established method in the industry for the preparation of films over large-surface substrates, including temperature-sensitive ones (i.e., scaling up at a low cost) [8]. Several reports can be found in the literature regarding the control of the emittance of VO 2 -based structures for applications such as smart radiator devices.…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…More recently, Kolenaty et al [13] demonstrated that when an HiPIMS-deposited VO 2 film was doped with W, multilayer smart windows with a thermochromic transition temperature of around 20-21 • C could be fabricated. Doping with W involved the use of DC sputtering concurrently with HiPIMS, offering more flexibility in terms of controlling the doping content in VO 2 films, and the processing temperature of the W-doped VO 2 was 330 • C. These results are important not only for the preparation of smooth films needed in optical devices, as demonstrated by Kolenaty et al, but also because magnetron sputtering is a well-established method in the industry for the preparation of films over large-surface substrates, including temperature-sensitive ones (i.e., scaling up at a low cost) [8]. Several reports can be found in the literature regarding the control of the emittance of VO 2 -based structures for applications such as smart radiator devices.…”
Section: Introductionmentioning
confidence: 89%
“…As for the materials used for the individual layers, I decided to consider SiO 2 and a-Si deposited by PECVD not only because they are both readily available as they are widely used in technological applications, but also due to the important contrast between their refractive indices, allowing the achievement of the desired reflection over a large bandwidth [8]. In addition, SiO 2 acts as a protective barrier layer between VO 2 and a-Si [32].…”
Section: Design Of the Additional Top Distributed Bragg Reflectormentioning
confidence: 99%
See 1 more Smart Citation
“…The phase transition is always accompanied by a structural transition from the monoclinic (M) phase to the rutile (R) phase, which has potential applications in infrared switches [ 3 ], smart thermal control devices [ 4 ] and smart windows [ 5 ]. In previous studies, researchers have paid more attention to the optimization of thermal, optical and electrical properties after phase transition [ 6 ], while mechanical properties have been almost ignored [ 7 ]. In fact, phase transition will cause the lattice to expand by 1% along the c R -direction, and to shrink by 0.6% and 0.1% along the a R -axis and b R -axis in the meanwhile [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Regardless of the method, high growth temperatures (450–800 °C) are employed to assure its stoichiometry [ 16 , 17 , 18 , 19 ], which is crucial in the synthesis of VO 2 thin films that display a sharp phase transition. However, instrumentation that delivers high substrate temperatures ( T S ) is costly and not industry-friendly [ 20 ]. For this reason, there have been numerous efforts to bring the T S down to more practical temperatures [ 21 , 22 , 23 , 24 , 25 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%